Cement dispersant
A water-soluble vinyl copolymer with a specific molecular structure addresses the challenges of flowability, flow retention, and initial strength in fluoride-containing cement formulations, delivering improved performance and economic benefits.
Patent Information
- Application Number
- JP2023179886
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
Conventional cement dispersants fail to adequately maintain flowability, flow retention, and initial strength development in cement formulations containing inorganic fluoride, leading to quality and economic issues.
A water-soluble vinyl copolymer with a specific molecular framework, comprising monomers A, B, C, and D, is used as a cement dispersant. This copolymer is obtained through aqueous solution polymerization with a controlled copolymerization ratio and molecular weight, incorporating sulfonic acid groups, short chain ester groups, and a balance of long and short PEG chains.
The cement dispersant achieves excellent flowability, reduced slumps, and enhanced initial strength of hardened concrete, even in formulations with fluoride, while maintaining construction efficiency and economic viability.
Smart Images

Figure 2025060341000001 
Figure 2025060341000002 
Figure 2025060341000003
Abstract
Description
Detailed Description of the Invention [Technical field]
[0001] The present invention relates to a cement dispersant. More specifically, the present invention relates to a cement dispersant that can ensure high quality even in a cement blend using a cement containing an inorganic fluoride (hereinafter referred to as fluoride) as a flux newly added in the cement manufacturing process. [Background technology]
[0002] In recent years, a technique of adding fluoride as a flux to lower the burning temperature for the purpose of saving energy in the cement manufacturing process has been known. However, when the cement containing the fluoride is used to mix a cement mixture using a conventional cement dispersant (e.g., Patent Documents 1, 2, 3, and 4) mainly composed of a conventional water-soluble vinyl copolymer, the initial fluidity and fluidity retention over time of the ready-mixed concrete (hereinafter referred to as fresh concrete) tend to decrease (hereinafter referred to as slump loss) compared with a cement not containing fluoride, and in order to secure the target fluidity, it is necessary to add a considerably large amount of the conventional cement dispersant, which causes problems in terms of quality and economy, such as a delay in setting time and a decrease in the initial strength of the hardened concrete.
[0003] In view of these circumstances, some proposals have been disclosed for obtaining excellent fluidity by adding cement additives when mixing a cement composition containing fluoride to produce fresh concrete (e.g., Patent Documents 5 and 6).
[0004] However, when a cement mixture is actually prepared using cement in which the fluoride of the flux remains, even if a conventionally known polycarboxylic acid cement dispersant (or additive) is used, the performance of the role that the dispersant itself should play (the performance of combining the three performances of initial fluidity, fluidity retention, and early strength development, hereinafter referred to as the present purpose) is not sufficient, and there is a demand for a proposal of a new cement dispersant that combines the performance of these three items and is excellent in practicality and economy. In other words, when a cement mixture is prepared using various conventionally known cement dispersants for this purpose, there is a problem that the conventionally known cement dispersants each have their own problems and do not provide fully satisfactory performance. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 59-18338 (Patent Publication) [Patent Document 2] Special Publication No. 5-11057 (Patent Publication) [Patent Document 3] JP 11-171619 A (Patent Publication) [Patent Document 4] JP 2003-2720 (Patent Publication) [Patent Document 5] JP 2017-178775 (Patent Publication) [Patent Document 6] JP 2017-222553 (Patent Publication) DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0006] The problem to be solved by the present invention is to provide a new cement dispersant which can exhibit improved performance, including flowability, flow retention, and early strength development of the hardened body, even in cement compositions such as fluoride-containing mortar and concrete. [Means for solving the problem]
[0007] As a result of research conducted by the inventors to solve the above problems, they discovered that a cement dispersant consisting of a water-soluble vinyl copolymer having a specific molecular skeleton is a suitable solution to meet the above requirements.
[0008] That is, the present invention relates to a cement dispersant which is used by adding 0.05 to 2.5 parts by mass to 100 parts by mass of cement, and which is a copolymer obtained by aqueous solution polymerization of at least a monomer A shown in Chemical formula 1 below, a monomer B shown in Chemical formula 2 below, a monomer C shown in Chemical formula 3 below, and a monomer D shown in Chemical formula 4 below, and which has a copolymerization ratio converted to monomers represented by Chemical formula 1 / monomer B shown in Chemical formula 2 / monomer C shown in Chemical formula 3 / monomer D shown in Chemical formula 4=55 to 88 / 0.5 to 10 / 0.5 to 10 / 8 to 25 (mol %, total 100), and which is composed of a water-soluble vinyl copolymer having a mass average molecular weight in the range of 3,000 to 100,000.
[0009] [ka] [ka] [ka] [ka]
[0010] (In Chemical Formula 1 to Chemical Formula 4, R 1 ,R 2 ,R 1 ,R 3 ,R 4 ,:H or CH 3 . R 5 : An alkyl group having 1 to 3 carbon atoms. M 1 :Hydrogen or an alkali metal or an alkaline earth metal. n: an integer between 1 and 3. m: An integer between 4 and 95.
[0011] The water-soluble vinyl copolymer of the present invention is a water-soluble vinyl copolymer obtained by aqueous radical copolymerization of monomer A represented by Chemical formula 1, monomer B represented by Chemical formula 2, monomer C represented by Chemical formula 3, and monomer D represented by Chemical formula 4 as essential components.
[0012] Examples of the monomer A represented by Chemical formula 1 include 1) methacrylic acid or an alkali metal salt or an alkaline earth metal salt of methacrylic acid, and 2) acrylic acid or an alkali metal salt or an alkaline earth metal salt of acrylic acid. Among these, methacrylic acid and / or sodium methacrylic acid are preferred.
[0013] Examples of the monomer B represented by Chemical formula 2 include 1) alkali metal salts and alkaline earth metal salts of methallylsulfonic acid, and 2) alkali metal salts and alkaline earth metal salts of allylsulfonic acid. The purpose of using the monomer B is to adjust the molecular weight during polymerization of the vinyl copolymer, and to enhance the cement dispersion function by partially introducing sulfonic acid groups into the molecular skeleton to construct a copolymer with less setting retardation than the above-mentioned carboxylic acid group alone as an anion group. The introduction of sulfonic acid groups is one of the features of the present invention, and in the present invention, it is preferable to use sodium methallylsulfonate.
[0014] Examples of the monomer C represented by Chemical formula 3 include 1) ethylene glycol monoacrylate (hereinafter referred to as HEA), diethylene glycol monoacrylate, and triethylene glycol monoacrylate, and 2) ethylene glycol monomethacrylate (hereinafter referred to as HEMA), diethylene glycol monomethacrylate, and triethylene glycol monomethacrylate.
[0015] In the present invention, the reason for introducing (meth)acrylic acid monoesters as monomer C into the molecular skeleton of the vinyl copolymer is to utilize the property that when the vinyl copolymer is added to the cement formulation, the ester group is hydrolyzed over time by the alkaline component of the cement, increasing the ratio of the carboxyl group. In other words, it is used to impart a slump loss prevention function to the molecular skeleton of the copolymer itself. In the present invention, among them, the above-mentioned HEA, the above-mentioned HEMA, and diethylene glycol monomethacrylate are preferred.
[0016] Further, as monomer D shown in Chemical Formula 4, two types of alkoxy (having 1 to 3 carbon atoms) polyethylene glycol (meth)acrylate monomers with different molar lengths can be used within the range where the added molar number of ethylene oxide is 4 to 95, preferably 5 to 85.
[0017] Specifically, within the range of the added molar number (m) of ethylene oxide contained in monomer D, a monomer in the range of 5 to 30 moles (referred to as monomer E) and a monomer in the range of 31 to 85 moles (referred to as monomer F), two types of monomer components, are preferably contained together during the copolymerization reaction with other comonomers within a predetermined ratio (however, the copolymerization molar ratio of E and F is E < F). The reason is considered important for maintaining the balance of the cement dispersion performance having dispersion retention performance. Based on the knowledge that a vinyl copolymer with a long polyoxyethylene graft chain (hereinafter referred to as a PEG chain) has a faster adsorption rate to cement particles and better initial dispersion performance than a vinyl copolymer with a short PEG chain, but has inferior dispersion retention performance over time. That is, as one of the features of the present invention, the property that a dispersion skeleton having a relatively long PEG chain and a relatively short PEG chain in the molecular structure of the vinyl copolymer has a function of appropriately controlling the adsorption rate of the vinyl copolymer to cement particles is utilized.
[0018] The water-soluble vinyl copolymer of the present invention can be obtained by radical copolymerizing vinyl monomers containing structural units A to D (wherein monomer D includes monomer E and monomer F) in a predetermined copolymerization ratio in the presence of a radical initiator. The radical copolymerization can be carried out in an aqueous solution using a water-soluble radical initiator.
[0019] The copolymerization method for the water-soluble vinyl copolymer of the present invention may be, for example, the following two methods 1) or 2), and is not limited thereto. However, in the present invention, method 1) is preferred from the viewpoint of obtaining a copolymer having a relatively narrow range of molecular weight distribution. 1) In advance, in a mixing vessel, each of the specified vinyl monomers and a molecular weight regulator are dissolved and mixed in water to prepare an aqueous solution (G) containing 30 to 55 mass% of each vinyl monomer in total. Meanwhile, in a separate mixing vessel, an aqueous solution (H) of a radical initiator dissolved in water is prepared. Next, using a separate polymerization reaction vessel, the aqueous solutions (G) and (H) are dropped separately and simultaneously into the polymerization reaction vessel for a specified time under a nitrogen gas atmosphere, while a radical copolymerization reaction is continued under a nitrogen gas atmosphere at 60 to 75°C for 4 to 6 hours, thereby obtaining a water-soluble vinyl copolymer copolymerized at a high polymerization rate. 2) Each of the specified vinyl monomers and the molecular weight modifier is dissolved in water to prepare an aqueous solution containing 20 to 45 mass% of each vinyl monomer in total. Next, a radical initiator is added to the aqueous solution in a nitrogen gas atmosphere, and a radical copolymerization reaction is carried out at 55 to 70°C for 4 to 6 hours to obtain an aqueous solution of a water-soluble vinyl copolymer copolymerized at a high polymerization rate.
[0020] As the radical initiator, a water-soluble initiator such as a persulfate, such as potassium persulfate, sodium persulfate, or ammonium persulfate, or 2,2-azobis(2-amidinopropane) dihydrochloride can be used. Furthermore, an aqueous redox initiator in which hydrogen peroxide is combined with a reducing substance such as L-ascorbic acid or a sulfite can also be used.
[0021] As the molecular weight regulator, a water-soluble thiol-based chain transfer agent such as mercaptoethanol, thioglycolic acid, 3-mercaptopropionic acid, or thiomalic acid can be used. In the present invention, the (meth)allylsulfonate salt used as the monomer B is a substance that simply acts as a comonomer and exhibits properties as a weak chain transfer agent in aqueous radical polymerization, so it is preferable to use it in combination with a strong thiol-based chain transfer agent (e.g., 3-mercaptopropionic acid) that is compatible with it. The amount of the thiol-based chain transfer agent used is appropriately adjusted according to the target molecular weight of the copolymer.
[0022] The water-soluble vinyl copolymer of the present invention thus obtained has, as its constituent units, a copolymerization ratio calculated as monomers represented by monomer A / monomer B / monomer C / monomer D=55-88 / 0.5-10 / 0.5-10 / 8-25 (mol %, total 100).
[0023] Further, as the monomer D, it is preferable to use a monomer D(E+F) containing two kinds of monomers, namely, a monomer E having an added mole number of ethylene oxide in the range of 5 to 30 and a monomer F having an added mole number in the range of 31 to 80, and it is further preferable that the copolymerization ratio, converted into monomers, is monomer A / monomer B / monomer C / monomer D(E+F)=60-80 / 1-7 / 1-8 / 9-24 (mol%, total 100) as the specific copolymer for the present purpose. The mass average molecular weight of the vinyl copolymer is in the range of 3,000 to 100,000 (gel permeation chromatography (hereinafter GPC method, calculated as polyethylene glycol, the same applies below)), and preferably in the range of 5,000 to 80,000.
[0024] The water-soluble vinyl copolymer as a cement dispersant of the present invention is obtained by copolymerizing each of the vinyl monomers exemplified above in a predetermined ratio, and a copolymer having a copolymerization ratio and a mass average molecular weight outside the predetermined range does not provide the sufficient effect of the present invention. In this case, other monomers may be copolymerized as needed as long as the effect of the present invention is not impaired. For example, acrylic acid methyl ester and (meth)acrylamide can be mentioned, and these are usually used within a range of 10 mol% or less of the total monomers.
[0025] In addition, when preparing a cement mixture using the water-soluble vinyl copolymer of the present invention, other agents can be used in combination depending on the purpose. Such other additives include air entraining agents, antifoaming agents, shrinkage reducing agents, hardening accelerators, waterproofing agents, preservatives, etc. In addition, the method of use is preferably to add them together with the mixing water when preparing the cement mixture, but they can also be added to the cement mixture after it is prepared.
[0026] The cement dispersant of the present invention can be applied to cement mixtures such as mortar and concrete prepared using cement to which no fluoride is added, but the present invention can achieve the intended remarkable effect when the cement mixture is prepared using cement containing 0.1 to 10 mass% of fluoride. Note that the fluoride refers to inorganic fluorides, and non-ionic organic fluorine compounds such as fluororesins are excluded from the scope of the present invention.
[0027] Specific examples of fluoride components include KF, CaF2, NaF, BaF2, MgF2, Na2SiF2, MgSiF2, and the like. Among these, KF or CaF2 is most often used.
[0028] In the present invention, the type of cement includes Portland cement such as ordinary cement, early strength cement, and ultra-early strength cement. It can also be effectively used for mixed cements such as blast furnace slag cement and fly ash cement. The amount of the cement dispersant of the present invention is usually 0.05 to 2.5 parts by mass, preferably 0.1 to 2 parts by mass, calculated as solid, per 100 parts by mass of cement, and is added when mixing the cement mixture.
[0029] The cement dispersant of the present invention is constructed based on the synthesis of a water-soluble polymer having a specific molecular structure as a function-imparting agent, and its characteristics can be summarized as 1) to 3) below. That is, it is characterized by incorporating the following synthesis requirements: 1) the use of monomer B to introduce a sulfonic acid group into the molecular skeleton, 2) the use of monomer C to introduce a short-chain ester group that is easily hydrolyzed over time by an alkaline component that precipitates at the cement hydration stage into the molecular skeleton, and 3) the use of monomer D to introduce a relatively long PEG chain and a relatively short PEG chain into the molecular skeleton. Effect of the Invention
[0030] According to the present invention, the cement dispersant of the present invention is excellent in exhibiting the intended effect not only for cement mixtures of normal concrete having a water / cement ratio of more than 50% but also for cement mixtures of high-strength concrete having a water / cement ratio of 30 to 40%. That is, for both normal-strength fresh concrete and high-strength fresh concrete, the dispersant has the effect of imparting excellent fluidity with a small amount of addition, resulting in less slump loss and excellent workability, while at the same time providing excellent early strength development of the concrete hardened body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The present invention includes the following embodiments 1) to 5). 1) A water-soluble vinyl copolymer (P-1) having a weight average molecular weight of 39,000, containing 70 mol % of structural unit A composed of sodium methacrylate, 3 mol % of structural unit B composed of sodium methallylsulfonate, 4 mol % of ethylene glycol monoacrylate structural unit C, 6 mol % of structural unit E composed of methoxypoly (addition mole number 10 moles) ethylene glycol methacrylate, and 17 mol % of structural unit F composed of methoxypoly (addition mole number 45 moles) ethylene glycol methacrylate (total D of E and F is 23 mol %, total of all structural units A to D is 100%).
[0032] 2) A water-soluble vinyl copolymer (P-2) having a mass average molecular weight of 41,000, containing 70 mol % of structural unit A composed of sodium methacrylate, 3 mol % of structural unit B composed of sodium methallylsulfonate, 4 mol % of ethylene glycol monomethacrylate structural unit C, 6 mol % of structural unit E composed of methoxypoly (addition mole number 10 moles) ethylene glycol methacrylate, and 17 mol % of methoxypoly (addition mole number 45 moles) ethylene glycol methacrylate F (total of D of E and F is 23 mol %, total of all structural units A to D is 100%).
[0033] 3) A water-soluble vinyl copolymer (P-3) having a mass average molecular weight of 57,000, containing 76 mol% of structural unit A composed of sodium methacrylate, 6 mol% of structural unit B composed of sodium methallylsulfonate, 4 mol% of structural unit C composed of ethylene glycol monomethacrylate, 3 mol% of structural unit E composed of methoxypoly (number of moles added: 20 moles) ethylene glycol methacrylate, and 11 mol% of F composed of methoxypoly (number of moles added: 68 moles) ethylene glycol methacrylate (total D of structural units E and F: 14 mol%, total of all structural units A to D: 100%).
[0034] 4) A water-soluble vinyl copolymer (P-4) having a mass average molecular weight of 59,500, in which the total structural units contain 76 mol% of structural unit A composed of sodium methacrylate, 6 mol% of structural unit B composed of sodium methallylsulfonate, 4 mol% of structural unit C composed of ethylene glycol monoacrylate, 3 mol% of structural unit E composed of methoxypoly (addition mole number 20 moles) ethylene glycol methacrylate, and 11 mol% of F composed of methoxypoly (addition mole number 68 moles) ethylene glycol methacrylate (total D of E and F: 14 mol%) (total of all structural units A to D: 100%).
[0035] 5) A water-soluble vinyl copolymer (P-5) having a weight average molecular weight of 36,200, containing 60 mol% of a structural unit composed of sodium methacrylate and 10 mol% of two types of structural units composed of sodium acrylate (70 mol% in total of structural units A), 3 mol% of a structural unit composed of sodium methallyl sulfonate and 3 mol% of a structural unit composed of sodium allyl sulfonate (6 mol% in total of structural units B), 4 mol% of a structural unit C composed of ethylene glycol monomethacrylate, 7 mol% of a structural unit E composed of methoxypoly (10 moles added) ethylene glycol methacrylate, and 16 mol% of a structural unit F composed of methoxypoly (45 moles added) ethylene glycol methacrylate (total of E and F: 23 mol%, total of all structural units A to D: 100%).
[0036] In the following, examples will be given to more specifically illustrate the configuration and effects of the present invention, but the present invention is not limited to these examples. In the following examples, % means % by mass, and parts means parts by mass, unless otherwise specified. EXAMPLES
[0037] Test Category 1 (Synthesis of Water-soluble Vinyl Copolymers) Examples 1 to 5 Water-soluble vinyl copolymer (P-1) Meanwhile, 62 parts (0.72 mol) of methacrylic acid, 5.2 parts (0.03 mol) of sodium methallylsulfonate, 5.2 parts (0.03 mol) of ethylene glycol monoacrylate, 31 parts (0.06 mol) of methoxypoly (addition mole number 10 mol) ethylene glycol methacrylate, 416 parts (0.20 mol) of methoxypoly (addition mole number 45 mol) ethylene glycol methacrylate, 2.4 parts of 3-mercaptopropionic acid, 230 parts of water, and 45 parts of a 30% aqueous solution of sodium hydroxide were added to a monomer mixing vessel V1, and the mixture was stirred to mix and dissolve. On the other hand, 62 parts of water, 7 parts of sodium persulfate, and 1.2 parts of 3-mercaptopropionic acid were charged into a radical initiator dissolving and mixing vessel V2, and mixed and dissolved uniformly. Next, 120 parts of water was charged into the polymerization reactor V3, and the atmosphere was then replaced with nitrogen. The temperature of the reaction system was maintained at 70° C. with stirring, and the solution was added dropwise from mixing vessel V1 to reaction vessel V3 over a period of 3 hours using a metering pump. At the same time, the solution was dropped into the reactor V3 from a mixing vessel V2 on a separate route over a period of 4 hours using a metering pump. After the dropwise addition, the mixture was aged for 2 hours to complete the polymerization reaction. The temperature of the reaction system was then cooled to 40°C, and 15 parts of a 30% aqueous solution of sodium hydroxide was added to neutralize the acid decomposition product, yielding a reaction product with a polymerization rate of 98% or more.
[0038] When this reaction product was analyzed by NMR, GPC (gel permeation), water content, loss on drying, etc., it was found to be a water-soluble vinyl copolymer (P-1) with a mass average molecular weight of 39,000, containing, among all the structural units, the structural units formed from sodium methacrylate / structural units formed from sodium methallylsulfonate / structural units formed from ethylene glycol monoacrylate / structural units formed from methoxypoly (number of moles added: 10) ethylene glycol methacrylate / structural units formed from methoxypoly (number of moles added: 45) ethylene glycol methacrylate in a ratio of 70 / 3 / 4 / 6 / 17 (mol %, total of all structural units: 100 mol %).
[0039] Water-soluble vinyl copolymer (P-2) It was synthesized in the same manner as the vinyl copolymer (P-1) and analyzed. As a result, it was found to be a water-soluble vinyl copolymer (P-2) having a mass average molecular weight of 41,000 and having, among all the structural units, the ratio of structural units formed from sodium methacrylate / structural units formed from sodium methallylsulfonate / structural units formed from ethylene glycol monomethacrylate / structural units formed from methoxypoly (number of moles added: 10)ethylene glycol methacrylate / structural units formed from methoxypoly (number of moles added: 45)ethylene glycol methacrylate = 70 / 3 / 4 / 6 / 17 (mol %, total of all structural units is 100 mol %).
[0040] Water-soluble vinyl copolymer (P-3) On the other hand, 76 parts (0.88 moles) of methacrylic acid, 11 parts (0.07 moles) of sodium methallylsulfonate, 6 parts (0.05 moles) of ethylene glycol monoacrylate, 34 parts (0.03 moles) of methoxypoly (addition mole number 10 moles) ethylene glycol methacrylate, 393 parts (0.12 moles) of methoxypoly (addition mole number 68 moles) ethylene glycol methacrylate, 3 parts of 3-mercaptopropionic acid, 230 parts of water, and 55 parts of a 30% aqueous solution of sodium hydroxide were added to the monomer mixing vessel V1, and stirred to mix and dissolve. On the other hand, 62 parts of water, 7 parts of sodium persulfate, and 1 part of 3-mercaptopropionic acid were added to the radical initiator dissolving and mixing vessel V2, and mixed and dissolved uniformly. Next, 174 parts of water were added to the polymerization reaction apparatus V3, and the atmosphere was replaced with nitrogen. The temperature of the reaction system was kept at 70°C while stirring, and the solution was dropped from the mixing vessel V1 to the reaction vessel V3 over a period of 3 hours using a metering pump. At the same time, the solution was dropped from the mixing vessel V2 on a separate route to the reaction vessel V3 over a period of 4 hours using a metering pump. After the dropwise addition, the mixture was aged for 2 hours to complete the polymerization reaction. Next, the temperature of the reaction system was cooled to 40°C, and then 15 parts of a 30% aqueous solution of sodium hydroxide was added to neutralize the acid decomposition product, resulting in a reaction product with a polymerization rate of over 98%.
[0041] When this reaction product was analyzed by the same method as above, it was found to be a water-soluble vinyl copolymer (P-3) with a mass average molecular weight of 57,000, containing, among all the structural units, the structural units formed from sodium methacrylate / structural units formed from sodium methallylsulfonate / structural units formed from ethylene glycol monomethacrylate / structural units formed from methoxypoly (number of moles added: 20) ethylene glycol methacrylate / structural units formed from methoxypoly (number of moles added: 68) ethylene glycol methacrylate in a ratio of 76 / 6 / 4 / 3 / 11 (mol %, total of all structural units: 100 mol %).
[0042] Water-soluble vinyl copolymer (P-4) As a result of synthesizing and analyzing in the same manner as the vinyl copolymer (P-3), it was found that the water-soluble vinyl copolymer (p-4) had a mass average molecular weight of 59,500 and contained, among all the structural units, structural units formed from sodium methacrylate / structural units formed from sodium methallylsulfonate / structural units formed from ethylene glycol monoacrylate / structural units formed from methoxypoly (number of moles added: 20) ethylene glycol methacrylate / structural units formed from methoxypoly (number of moles added: 68) ethylene glycol methacrylate in a ratio of 76 / 6 / 4 / 3 / 11 (mol %, total of all structural units is 100 mol %).
[0043] Water-soluble vinyl copolymer (P-5) The water-soluble vinyl copolymer (P-5) was obtained by synthesizing and analyzing in the same manner as the above (P-1) to (P-4). The details of each water-soluble vinyl copolymer are summarized in Table 1.
[0044] Comparative Examples 1 to 6 Water-soluble vinyl copolymers (Pr-1)~(Pr-6) The water-soluble vinyl copolymers (Pr-1) to (Pr-6) were synthesized and analyzed in the same manner as the water-soluble vinyl copolymers in the above Examples. The details of each water-soluble vinyl copolymer are summarized in Table 1.
[0045] [Table 1]
[0046] In Table 1, *1: Sodium methacrylate *2: Sodium acrylate *3: Sodium methallyl sulfonate *4: Sodium allylsulfonate *5: Ethylene glycol monoacrylate *6: Ethylene glycol monomethacrylate *7: Methoxypoly (addition mole number 10 moles) ethylene glycol methacrylate ester *8: Methoxypoly (addition mole number 20 moles) ethylene glycol methacrylate ester *9: Methoxypoly (addition mole number 45 moles) ethylene glycol methacrylate ester *10: Methoxypoly (addition mole number 68 moles) ethylene glycol methacrylate ester *11: Methoxypoly (addition mole number 120 moles) ethylene glycol methacrylate ester
[0047] Test Category 2 (Preparation and Evaluation of Concrete) Test Examples 1 to 5 of the Example Using the water-soluble vinyl copolymer (p-1) of the present invention prepared in Test Section 1 and shown in Table 1, ordinary Portland cement (density = 3.16 g / cm3) was mixed in a 50-liter pan-type forced mixer under the mixing conditions (mixture number 1) shown in Table 2. 3 , 1 part of CaF2 was added to 100 parts of cement), fine aggregate (river sand, density = 2.58 g / cm 3 ), mixing water (tap water) and the required amount of air content adjuster were added and mixed for 90 seconds until the slurry was uniform. Next, coarse aggregate (crushed stone, density = 2.68 g / cm 3) was added and mixed for 60 seconds. The water content contained in the water-soluble vinyl copolymer of the present invention was added while being diluted with the mixing water as a part of the mixing water, and concrete of Test Example 1 with a target slump of 18±1 cm and a target air content of 4±1% was prepared. Similarly, concretes of Test Examples 2 to 5 were prepared using the vinyl copolymers (P-2) to (P-5) shown in Table 1. All test examples were carried out under temperature and humidity control of a mixing temperature of 20°C and a relative humidity of 60%.
[0048] Test Examples 6 to 10 of the Examples Using the vinyl copolymer (P-1) prepared in Test Section 1 and shown in Table 1, ordinary Portland cement (density = 3.16 g / cm3) was mixed in a 50-liter pan-type forced mixer under the mixing conditions (mixture number 2) shown in Table 2. 3 , 1 part of KF reagent was added to 100 parts of cement), fine aggregate (river sand, density = 2.58 g / cm 3 ), mixing water (tap water) and the required amount of air content adjuster were added and mixed for 90 seconds until the slurry was uniform. Next, coarse aggregate (crushed stone, density = 2.68 g / cm 3 ) was added and mixed for 60 seconds. The water contained in the water-soluble vinyl copolymer of the present invention was added while being diluted with the mixing water as a part of the mixing water, and concrete of Test Example 6 with a target slump of 21±1 cm and a target air content of 4±1% was prepared. Similarly, concrete of Test Examples 7 to 10 was prepared using (P-2) to (P-5) shown in Table 1. All test examples were carried out under temperature and humidity control of mixing temperature 20°C and RH 60%.
[0049] Test Examples 11 to 13 of the Example Using the vinyl copolymer (P-1) prepared in Test Section 1 and shown in Table 1, ordinary Portland cement (density = 3.16 g / cm3) was mixed in a 50-liter pan-type forced mixer under the mixing conditions (mixture number 3) shown in Table 2. 3 ), fine aggregate (river sand, density = 2.58g / cm 3), mixing water (tap water) and the required amount of air content adjuster were added and mixed for 90 seconds until the slurry was uniform. Next, coarse aggregate (crushed stone, density = 2.68 g / cm 3 ) was added and mixed for 60 seconds. The water content contained in the water-soluble vinyl copolymer of the present invention was added while being diluted with the mixing water as a part of the mixing water, and concrete of Test Example 11 with a target slump of 21±1 cm and a target air content of 4±1% was prepared. Similarly, concretes of Test Examples 12 to 13 were prepared using the copolymer (P-3) and the copolymer (P-5) shown in Table 1. All the test examples were carried out under temperature and humidity control of a mixing temperature of 20°C and a relative humidity of 60%.
[0050] The test results of fresh concrete in Test Examples 1 to 5, 6 to 10, and 11 to 13 are summarized in Table 3, and the test results of hardened concrete are summarized in Table 4.
[0051] [Table 2]
[0052] In Table 2, *1: Ordinary Portland cement (density = 3.16 / cm 3 ) *2: Fine aggregate (river sand, density = 2.58g / cm 3 ) *3: Coarse aggregate (crushed stone, density = 2.68g / cm 3 ) *4: Cement was used with 1 part CaF2 added to 100 parts of cement. *5: Cement was used with 1 part KF added to 100 parts of cement. *6: Fluoride-free cement
[0053] -Evaluation of concrete properties The concrete of each example prepared was evaluated for slump, air content, and compressive strength immediately after mixing and after leaving for 90 minutes using the methods described below. The results of the physical property tests of the composite products of the examples and the physical property tests of the comparative products of the comparative examples are summarized in the table below.
[0054] Slump (cm): Measured in accordance with JIS-A1101 for concrete immediately after mixing and after leaving to stand for 90 minutes. Slump remaining rate (%): Slump value after standing for 90 minutes / Slump value immediately after mixing) x 100. Air content (volume %): Measured in accordance with JIS-A1128 for concrete immediately after mixing and after leaving to stand for 90 minutes. Compressive strength (N / mm 2 ):Measurements were carried out in accordance with JIS-A1108 for hardened specimens aged 1 day, 3 days, and 28 days.
[0055] [Table 3]
[0056] [Table 4]
[0057] In Tables 3 and 4, *1: Formulation number listed in Table 2 *2: Water-soluble vinyl copolymers listed in Table 1 *3: Parts of water-soluble vinyl copolymer (solid equivalent) added per 100 parts by mass of cement
[0058] Comparative Examples Test Examples 14 to 19 In a manner similar to that of Test Example 1, concretes of Test Examples 15 to 20 were prepared using Comparative Examples 1 to 6 (Pr-1 to Pr-6) shown in Table 1 under the mix conditions (Mixture No. 1) shown in Table 2.
[0059] Comparative Example Test Examples 20 to 25 In a manner similar to that of Test Example 6, concretes of Test Examples 20 to 25 were prepared under the mix conditions (mix number 2) shown in Table 2 using Comparative Examples 1 to 6 (Pr-1 to Pr-6) shown in Table 1.
[0060] Comparative Examples 26-27 In a manner similar to that of Test Example 15, concretes of Test Examples 29 to 30 were prepared under the mix conditions (mix number 3) shown in Table 2 using Comparative Examples 1 and 3 (Pr-1 and Pr-3) shown in Table 1.
[0061] The test results of fresh concrete in Test Examples 14 to 27 are summarized in Table 5, and the test results of hardened concrete are summarized in Table 6.
[0062] [Table 5]
[0063] [Table 6]
[0064] In Tables 5 and 6, *1: Formulation number listed in Table 2 *2: Water-soluble vinyl copolymers listed in Table 1 *3: Addition mass parts of water-soluble vinyl copolymer (solid content equivalent) per 100 mass parts of cement *4: Not measured as it had not hardened.
[0065] As is already clear from the results of Tables 1 to 6, the concrete prepared using the cement dispersant made of the water-soluble vinyl copolymer of the present invention clearly has the intended effect of imparting high fluidity to fresh concrete, reducing slump loss, and at the same time, exhibiting excellent early strength development of the concrete hardened body, even when ordinary Portland cement containing fluoride is used. Furthermore, it has the characteristic that it can be fully applied even when cement not containing fluoride is used.
Claims
1. A cement dispersant is used by adding 0.05 to 2.5 parts by mass to 100 parts by mass of cement, and is a copolymer obtained by aqueous solution polymerization of at least a monomer A shown in Chemical formula 1 below, a monomer B shown in Chemical formula 2 below, a monomer C shown in Chemical formula 3 below, and a monomer D shown in Chemical formula 4 below, the copolymerization ratio converted into monomers being represented by the following monomer A shown in Chemical formula 1 / monomer B shown in Chemical formula 2 / monomer C shown in Chemical formula 3 / monomer D shown in Chemical formula 4=55 to 88 / 0.5 to 10 / 0.5 to 10 / 8 to 25 (mol %, total 100), and the dispersant is a water-soluble vinyl copolymer having a mass average molecular weight in the range of 3,000 to 100,000. 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】 (In Chemical Formula 1 to Chemical Formula 4, R 1 , R 2 , R 1 , R 3 , R 4 , : H or CH 3 . R 5 : an alkyl group having 1 to 3 carbon atoms. M 1 : Hydrogen or an alkali metal or an alkaline earth metal. n: an integer from 1 to 3. m: an integer from 4 to 95.
2. The cement dispersant according to claim 1, wherein the monomer D represented by Chemical formula 4 is a mixture containing two kinds of monomers, a monomer having an added mole number of ethylene oxide in the range of 5 to 30 and a monomer having an added mole number in the range of 31 to 80.
3. 3. The cement dispersant according to claim 1, wherein the monomer B represented by the formula 2 is sodium methallyl sulfonate.
4. The cement dispersant according to any one of claims 1 to 3, wherein the monomer C represented by Chemical formula 3 is at least one selected from the group consisting of ethylene glycol acrylic acid monoester and ethylene glycol methacrylic acid monoester.
5. The cement dispersant according to any one of claims 1 to 4, wherein the copolymerization ratio is: Monomer A represented by Chemical formula 1 / Monomer B represented by Chemical formula 2 / Monomer C represented by Chemical formula 3 / Monomer D represented by Chemical formula 4 = 60 to 80 / 1 to 7 / 1 to 8 / 9 to 24 (mol%, total 100).
6. The cement dispersant according to any one of claims 1 to 5, which is a water-soluble vinyl copolymer having a mass average molecular weight in the range of 5,000 to 80,000.
7. The cement dispersant according to any one of claims 1 to 6, wherein the cement contains 0.1 to 10 mass% of an inorganic fluoride component, and the dispersant is added when the cement mixture is mixed.
8. The cement dispersant according to any one of claims 1 to 7, which is added to a cement containing at least one inorganic fluoride selected from the group consisting of KF, CaF2, NaF, BaF2, MgF2, Na2SiF2, and MgSiF2.
Citation Information
Patent Citations
Anti-freezing device of hot water supplier
JP1984018338A
Radiation-spectrum measuring apparatus
JP1993011057A
Dispersing agent for cement
JP1999171619A
Cement dispersing agent
JP2003002720A
Additive for cement
JP2017178775A